2015
DOI: 10.1007/s12031-015-0652-0
|View full text |Cite
|
Sign up to set email alerts
|

Examination of PACAP-Like Immunoreactivity in Urogenital Tumor Samples

Abstract: Numerous studies investigated the localization of pituitary adenylate cyclase-activating polypeptide (PACAP) and its receptors in different tumors and described the effects of analogs on tumor growth to show its potential role in oncogenesis. Recently, our research group has found significantly lower levels of PACAP27-like immunorreactivity (LI) and PACAP38-LI in different human samples of primary small cell lung cancer and colon cancer compared to normal healthy tissues. There are only few human studies showi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…Interestingly, unlike in other tissues, PACAP38 and 27 were found to have the same levels in human testis as shown by radioimmunoassay (Tamas et al 2016). No differences were found in the level of PACAP peptides between normal tissues and seminomas (Tamas et al 2016), but a different distribution pattern was observed in different tumor biopsies by Nakamura et al (2014). In addition to the local production of PACAP, circulating PACAP can additionally contribute to testicular functions of the peptide, as it has been shown that PACAP can cross the blood-testis barrier (Banks et al 1993, Mizushima et al 2001.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Interestingly, unlike in other tissues, PACAP38 and 27 were found to have the same levels in human testis as shown by radioimmunoassay (Tamas et al 2016). No differences were found in the level of PACAP peptides between normal tissues and seminomas (Tamas et al 2016), but a different distribution pattern was observed in different tumor biopsies by Nakamura et al (2014). In addition to the local production of PACAP, circulating PACAP can additionally contribute to testicular functions of the peptide, as it has been shown that PACAP can cross the blood-testis barrier (Banks et al 1993, Mizushima et al 2001.…”
Section: Discussionmentioning
confidence: 53%
“…A testis-specific splice variant of the PAC1 receptor has also been reported (Daniel et al 2001). Interestingly, unlike in other tissues, PACAP38 and 27 were found to have the same levels in human testis as shown by radioimmunoassay (Tamas et al 2016). No differences were found in the level of PACAP peptides between normal tissues and seminomas (Tamas et al 2016), but a different distribution pattern was observed in different tumor biopsies by Nakamura et al (2014).…”
Section: Discussionmentioning
confidence: 61%
“…In another recent study, no alterations in PACAP-LI between healthy and tumoral samples from the urinary bladder and testis were detected, but lower PACAP38-LI was found in kidney tumors compared with healthy tissue samples, and higher PACAP27-LI in prostatic cancer compared to samples from benign prostatic hyperplasia [ 46 ]. These data indicate that PACAP levels of different tissue samples are altered under pathological conditions suggesting a potential role of PACAP on tumor growth [ 46 ]. Reduction of PACAPcontaining nerve fi bers was described in a few conditions, such as in women with polycystic ovaries [ 47 ].…”
Section: Concluding Remarks: Future Perspectives and Limitationsmentioning
confidence: 84%
“…Signifi cantly higher tissue levels were also shown in cardiac tissue obtained from patients with ischemic heart disease [ 45 ], while lower levels/downregulation were found in other diseases: in lung and colon cancer samples [ 45 ]. In another recent study, no alterations in PACAP-LI between healthy and tumoral samples from the urinary bladder and testis were detected, but lower PACAP38-LI was found in kidney tumors compared with healthy tissue samples, and higher PACAP27-LI in prostatic cancer compared to samples from benign prostatic hyperplasia [ 46 ]. These data indicate that PACAP levels of different tissue samples are altered under pathological conditions suggesting a potential role of PACAP on tumor growth [ 46 ].…”
Section: Concluding Remarks: Future Perspectives and Limitationsmentioning
confidence: 94%
“…PACAP alterations have been observed in several diseases in both tissue samples and body fluids including plasma, cerebrospinal fluid and follicular fluid [16,49]. Recent studies have shown that PACAP levels were lower in lung cancer, colon and kidney tumor samples compared to healthy tissue, while higher in prostate cancer samples compared with samples from benign prostatic hyperplasia [50,51]. As PACAP is indicated as a potential biomarker for various conditions by several studies, it would be important to conduct a clinical study including enough pathological placenta samples to draw final conclusions (clinical review: see Reglodi et al in this book, chapter 2.…”
Section: Expression Of Pacap In Pathological Pregnanciesmentioning
confidence: 99%